Kehidupan Kedua dan Dorongan Naluriah: Studi Tentang Eros dan Thanatos dalam Anime ReLife - Syafnur, Zanuar Sholihul; Mulyadi, Budi (Vocational College of Diponegoro University, 2025)
This study aims to analyze the dynamics of the second life and instinctual drives in the anime ReLife using Sigmund Freud's psychoanalytic theory, specifically the concepts of Eros and Thanatos. ReLife narrates the journey of Arata Kaizaki, the main character who is given the opportunity to relive his youth through a scientific experiment. This research explores how the life drive (Eros), related to the desire for survival, love, and reproduction, competes with the death drive (Thanatos), which involves destructiveness, despair, and a tendency to return to a state of non-existence. By applying a narrative analysis method and a qualitative approach, this study found that ReLife symbolically depicts the struggle between Eros and Thanatos in Arata's inner conflict as he tries to start a new life while overcoming his past trauma. The results of this study indicate that ReLife not only portrays the character's struggle to rebuild his social life but also raises a deeper theme concerning the conflict between the life and death instincts in the context of modern life